Pengaruh Etnis, Pengetahuan Kewirausahaan dan Sumber Modal Terhadap Minat Berwirausaha Masyarakat di Kecamatan Rantepao dan Kecamatan Tallunglipu - Olivia Banne; Mince Batara; Rati Pundissing (CV. Ulil Albab Corp, 2024)
The study aims to test and analyze the influence of ethnicity, entrepreneurship knowledge and capital resources on the entrepreneurial interests of the community in the Rantepao district and Tallunglipu district. This research method is quantitative research, data collection technique through questionnaires. The population in this study was 7,218 and the sample of the study was 98 respondents, the method of sampling using the Slovin formula. The data were analyzed using the SPSS 22 program. The results of this study show that: (1) Ethnicity has a positive and significant influence on the interests of entrepreneurs in the Rantepao and Tallunglipu districts, (2) Entrepreneurship knowledge has a significant and positive influence upon the interest of entreprenors in Ranteapao district, (3) Capital resources are ineffective and insignificant in relation to entrepreneurial interests in the district and the Tallunglipu district; and (4) Ethnic knowledge, enterprise knowledge and capital resources combined have a significant positive impact on the entrepreneur interest of the community in the rantepo and the tallunglipo district. This means that every person of different ethnicities has a life spirit that has been planted from an early age so that a person's character can be formed through the surrounding environment, with corporate knowledge that encourages society to grow and innovate so that the undertakings that it undertakes have a long-term impact on its well-being and long-lasting, capital resources that are important to start as a small enterprise and determine a large enterprise